Phytochemical and Nutritional Quality Changes During Irrigation and Postharvest Processing of the Underutilized Vegetable African Nightshade - Sivakumar, Dharini; Phan, Anh Dao Thi; Slabbert, Retha M.; Sultanbawa, Yasmina; Remize, Fabienne (Frontiers in Nutrition, 2020)
Underutilised or traditional leafy vegetables are crops cultivated or grown either in the wild and mostly consumed as a nutritional accompaniment to staples, raw (fresh), cooked or in a dried form, by communities through custom, habit and tradition. These traditional leafy vegetables are considered natural rich sources of phytochemicals and nutritional compounds. However, overtime the keenness for consumption of traditional vegetables is becoming less popular. Poor nutrient diets are the main cause of mortality and morbidity especially in developing countries, where the problem is predominant due to poverty. Consumption of traditional vegetables can assist in preventing the development of chronic diseases as they contain various bioactive compounds that can exhibit multiple health benefits. Traditional leafy vegetables play a vital role in combatting hunger, food insecurity and malnutrition, and most are suitable for food intervention programmes. African nightshade (Solanum family) is one of the most commonly consumed traditional leafy vegetables. Communities often face a shortage of vegetables during the dry seasons, therefore preservation of the edible leaves is one of the developed strategies to help consumers to face these times of shortage. Solar drying and fermentation are adopted as traditional methods to extend the availability of African nightshade vegetables and to decrease levels of antinutritive compounds in theses vegetables. Moreover, the phytochemicals and nutritional compounds of African nightshade accessions are affected by the agronomy practices and postharvest processing methods. Thus, this mini review provides information on changes in phytochemicals, nutrition and antinutritive compounds with different postharvest processing methods and irrigation. The review also provides the justification to promote the cultivation, by identifying the potential African nightshade accessions that are rich in phytonutritional compounds to promote their consumption.